Novel Preparation of Fe Doped TiO2 Nanoparticles and Their Application for Gas Sensor and Photocatalytic Degradation - Sunil Babu Eadi; Sungjin Kim; Soon Wook Jeong; Heung Woo Jeon (Advances in Materials Science and Engineering)
The preparation of Fe doped TiO2 is demonstrated as well as application for gas sensing and photocatalytic degradation. Fe doped TiO2 nanopowder was prepared by the mechanochemical ball milling method. The results show the uniform doping of Fe in TiO2 powder. The average size of the particle is observed to be ~28 nm. The H2 gas sensor was fabricated using the Fe doped TiO2 nanopowder and the effect of Fe doping on the sensing properties is investigated with various temperature ranges. The prepared Fe doped TiO2 nanoparticles are also used to explore degradation properties of Rhodamine B dye under LED light.